The analysis of the clinical picture of hypothyroidism in menopausal women - Matuszek, Beata; Strawa-Zakościelna, Katarzyna; Pyzik, Aleksandra; Duma, Dariusz; Nowakowski, Andrzej; Paszkowski, Tomasz (Menopause Review/Przegląd Menopauzalny, 2010)
The objective of this retrospective study was to analyze the clinical picture of hypothyroidism in women, in relation to their menopausal status. Materials and methods : A total of 694 female ambulatory patients were divided into 3 groups: group I – 258 menstruating patients aged up to 45, group II – 124 perimenopausal patients aged between 46 and 52, group III – 312 postmenopausal patients aged over 52. Medical documentation of the patients with hypothyroidism was evaluated in terms of the selected features of their medical history and clinical picture of the disease. Results : The main cause of hypothyroidism was the chronic autoimmune thyroid gland inflammation; in group I it concerned 62.8% of patients, in the remaining two groups it was 50.0% and 51.6%, respectively. Analysing the prevalence of clinical symptoms it was found that the most frequent ones were: weight gain (18.6%), weakness (16.3%) and drowsiness (14.7%). In group II the prevailing symptoms were: hypertension (37.1%), weight gain (21.8%), drowsiness and weakness (12.1%) whereas in group III hypertension (60.3%), symptoms of ischemic heart disease (24.4%) and weight gain (14.4%) were dominant. Mean daily doses of levothyroxine used in the 3 groups of patients were 90 μg, 81 μg ,74 μg, respectively. In women from groups II and III, a lipid balance disorder (hypercholesterolemia) was observed significantly more often than in younger patients. Conclusions : Hyperthyroidism was diagnosed most frequently in postmenopausal women. The main cause of hypothyroidism was the chronic autoimmune thyroid gland inflammation. In postmenopausal women unusual clinical symptoms of hyperthyroidism dominated, which resulted from the coexistence of other diseases, mainly cardiovascular disorders. A 24-hour long-dose of levothyroxine in postmenopausal women was lower as compared to menstruating women. Hypercholesterolemia was a considerably frequent element of the clinical picture of hypothyroidism in postmenopausal women.